Importance of reference gene selection for articular cartilage mechanobiology studies. Issue 4 (April 2016) - Al-Sabah, A.; Stadnik, P.; Gilbert, S.J.; Duance, V.C.; Blain, E.J.
Summary: Objective: Identification of genes differentially expressed in mechano-biological pathways in articular cartilage provides insight into the molecular mechanisms behind initiation and/or progression of osteoarthritis (OA). Quantitative PCR (qPCR) is commonly used to measure gene expression, and is reliant on the use of reference genes for normalisation. Appropriate validation of reference gene stability is imperative for accurate data analysis and interpretation. This study determined in vitro reference gene stability in articular cartilage explants and primary chondrocytes subjected to different compressive loads and tensile strain, respectively. Design: The expression of eight commonly used reference genes ( 18s, ACTB, GAPDH, HPRT1, PPIA, RPL4, SDHA and YWHAZ ) was determined by qPCR and data compared using four software packages (comparative delta-Ct method, geNorm, NormFinder and BestKeeper). Calculation of geometric means of the ranked weightings was carried out using RefFinder. Results: Appropriate reference gene(s) for normalisation of mechanically-regulated transcript levels in articular cartilage tissue or isolated chondrocytes were dependent on experimental set-up. SDHA, YWHAZ and RPL4 were the most stable genes whilst glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and to a lesser extent Hypoxanthine-guanine phosphoribosyltransferase (HPRT), showed variable expression in response to load, demonstrating their unsuitability in such in vitro studies. The effect of using unstable reference genes to normalise the expression of aggrecan (ACAN) and matrix metalloproteinase 3 (MMP3) resulted in inaccurate quantification of these mechano-sensitive genes and erroneous interpretation/conclusions. Conclusion: This study demonstrates that commonly used 'reference genes' may be unsuitable for in vitro cartilage chondrocyte mechanobiology studies, reinforcing the principle that careful validation of reference genes is essential prior to each experiment to obtain robust and reproducible qPCR data for analysis/interpretation.